Testing platform for autonomous ground robot - Yong, We Seen. (2011)
This report document the modification process of Complex Programming Logic Device (CPLD) embedded wheeled robot for the EE3072 Project, Module P313 Semicustom IC Implementation. Currently, the wheeled robot that implemented by predecessor was unstable and bulky. In order to stabilize and reduce the size of the wheeled robot, modification needs to be done. The purpose of EE3072 Project, Module P313 Semicustom IC Implementation is allowing the student to design and download their VHDL coding for the wheeled robot. Each of the students will be assigned the robot path and speed module. The students need to design according to the assigned path and speed. CPLD featured in this robot uses Altera MAX7000 High-performance EEPROM-based programmable logic device (PLDs). The CPLD is embedded with one Microchip micro processors to reduce the student workload. The students are only required to design the robot path and speed. The project will also discuss the component used such as Infrared proximity sensors and Infrared Emitting LED. The new position of the servo motor will discussed. Analog component such as Infrared proximity sensors was replaced by digital Infrared proximity sensors, this will remove the analog to digital function. Sourcing of the hardware and development of the robot will be discussed in this report.